Fetal microchimerism and maternal health: A review and evolutionary analysis of cooperation and conflict beyond the womb. (28th August 2015) - Boddy, Amy M.; Fortunato, Angelo; Wilson Sayres, Melissa; Aktipis, Athena
<x xml:space="preserve">Abstract</x> The presence of fetal cells has been associated with both positive and negative effects on maternal health. These paradoxical effects may be due to the fact that maternal and offspring fitness interests are aligned in certain domains and conflicting in others, which may have led to the evolution of fetal microchimeric phenotypes that can manipulate maternal tissues. We use cooperation and conflict theory to generate testable predictions about domains in which fetal microchimerism may enhance maternal health and those in which it may be detrimental. This framework suggests that fetal cells may function both to contribute to maternal somatic maintenance (e.g. wound healing) and to manipulate maternal physiology to enhance resource transmission to offspring (e.g. enhancing milk production). In this review, we use an evolutionary framework to make testable predictions about the role of fetal microchimerism in lactation, thyroid function, autoimmune disease, cancer and maternal emotional, and psychological health. Also watch the Video Abstract.